2013
DOI: 10.5606/tjr.2013.2779
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Efficacy of Dry Needling, Lidocaine Injection, and Oral Flurbiprofen Treatments in Patients with Myofascial Pain Syndrome: A Double-Blind (For Injection, Groups Only), Randomized Clinical Trial

Abstract: Amaç: Bu çalışmada boyun ve sırt bölgesinde miyofasiyal ağrı sendromu (MAS) bulunan hastalarda kuru iğneleme, lidokain enjeksiyonu ve oral flurbiprofen tedavilerinin etkinliği karşılaştırıldı. Hastalar ve yöntemler:Bu prospektif çalışmaya toplam 60 hasta (7 erkek, 53 kadın; ort yaş 33.7 yıl; dağılım 18-50 yıl) dahil edildi. Hastalar blok randomizasyon ile üç gruba ayrıldı. Bir gruba tetik noktalara kuru iğneleme, bir gruba lidokain enjeksiyonu (çift kör) ve diğer gruba yedi gün süresince 200 mg/gün oral flurbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
0
22
0
2
Order By: Relevance
“…Relative treatment effect was explained as the probability that a randomly chosen observation from time point and/or group under consideration tends to result in a larger value than the randomly chosen observation from the whole data set independently from time point and/or group under consideration. 15 We used LD_F2 design to analyze the repeated measurements taken from the eyes of the patients. F1_LD_F1 design was used to analyze the repeated measurements taken from 3 subgroups of treatment eye of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Relative treatment effect was explained as the probability that a randomly chosen observation from time point and/or group under consideration tends to result in a larger value than the randomly chosen observation from the whole data set independently from time point and/or group under consideration. 15 We used LD_F2 design to analyze the repeated measurements taken from the eyes of the patients. F1_LD_F1 design was used to analyze the repeated measurements taken from 3 subgroups of treatment eye of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…24) Regarding the additional effects of injectates, many studies have shown no significant differences among groups of dry needling and wet needling using steroid, procaine or lidocaine, and botulinum toxin. 23,36,37) These findings implied that the main mechanism of the analgesic action of dry needling and even injection might be the disruption of comfort. Post-injection soreness was reported to be more intense and longer in dry needling than in injections with lidocaine.…”
Section: Clinical Proceduresmentioning
confidence: 93%
“…A intensidade da dor foi avaliada pela EAV e um questionário de qualidade de vida também foi avaliado. Estatisticamente, os três grupos apresentaram resultados favoráveis para os requisitos avaliados em termos de sensibilidade pré-intervenção 31 .…”
Section: P 110unclassified